2019
DOI: 10.1128/mcb.00273-19
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Specific Functional Evaluation of the Nrf2 and MafG Heterodimer by Introducing a Tethered Dimer into Small Maf-Deficient Cells

Abstract: A group of cytoprotective genes is regulated by heterodimers composed of the cap’n’collar (CNC) family member Nrf2 and one of the small Maf (sMaf) proteins (MafF, MafG, or MafK) through the antioxidant response element (ARE, also referred to as the CNC-sMaf binding element [CsMBE]). Many lines of evidence support this model; however, a direct and specific evaluation of the Nrf2-sMaf heterodimer remains to be executed. To address this issue, we constructed a tethered Nrf2-MafG (T-N2G) heterodimer using a flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…The global analysis of gene expression in different model systems confirmed that NRF2 directly regulates both the basal and inducible expression of a broad range of genes involved in the oxidative stress response (Table 2) (24,(32)(33)(34)(35)(36)(37). Furthermore, a comparison of chromatin immunoprecipitation sequencing (ChIP-Seq) analyses carried out on the CNC transcription factors revealed that although all family members bind to the same TGACNNNGC consensus motif, they mostly regulate the expression of nonoverlapping sets of genes, confirming the specific function of NRF2 in the oxidative stress response (38)(39)(40)(41)(42)(43)(44)(45).…”
Section: Nrf2 Modulates the Transcriptional Response To Phase II Inducers And Oxidative Stressmentioning
confidence: 71%
“…The global analysis of gene expression in different model systems confirmed that NRF2 directly regulates both the basal and inducible expression of a broad range of genes involved in the oxidative stress response (Table 2) (24,(32)(33)(34)(35)(36)(37). Furthermore, a comparison of chromatin immunoprecipitation sequencing (ChIP-Seq) analyses carried out on the CNC transcription factors revealed that although all family members bind to the same TGACNNNGC consensus motif, they mostly regulate the expression of nonoverlapping sets of genes, confirming the specific function of NRF2 in the oxidative stress response (38)(39)(40)(41)(42)(43)(44)(45).…”
Section: Nrf2 Modulates the Transcriptional Response To Phase II Inducers And Oxidative Stressmentioning
confidence: 71%
“…The Nrf2 pathway is a master regulator of cell resistance to oxidative injury [ 53 ] Keap1 is a cytoplasmic junction protein that may downregulate Nrf2. Normally, under physiological conditions, of low the activity of Nrf2 activity is maintained at a low level via its distribution in the cytoplasm in the Nrf2-keap1 complex [ 54 ]. After activation, Nrf2 is phosphorylated, dissociates from the complex, and is then released to translocate into the nucleus, where it induces downstream expression of HO-1 and SOD, which eliminate ROS [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Nrf2 pathway is a master regulator of cell resistance to oxidative injury [53] Keap1 is a cytoplasmic junction protein that may downregulate Nrf2. Normally, under physiological conditions, of low the activity of Nrf2 activity is maintained at a low level via its distribution in the cytoplasm in the Nrf2-keap1 complex [54]. After activation, Nrf2 is phosphorylated, dissociates from the complex, and is then released to translocate into the nucleus, where it induces downstream expression of HO-1 and SOD, which eliminate ROS [55].…”
Section: Discussionmentioning
confidence: 99%